Prediksi Financial Distress Model Almant Z-Score, Kinerja Keuangan dan Pengaruhnya terhadap Nilai Perusahaan - Silviyani, Yuli Anita; Risthi, Alyssa; Afandi, Agus (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The aim of this research is to predict financial distress conditions using the Almant Z-Score model and to test the influence of financial distress and financial performance on company value in basic industrial and chemical sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The sample selection technique is purposive sampling method, research data is secondary data obtained from the Indonesia Capital Market Directory for the period 2017 - 2021. The data analysis method used is multiple regression analysis with the eviews 12.0 application tool. The research results show that financial distress and debt to equity ratio (DER) partially do not have a significant effect on company value. Meanwhile, financial performance as proxied by return on assets (ROA) and return on equity (ROE) partially has a positive and significant effect on company value.